1975
DOI: 10.1111/j.1365-2222.1975.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Description and immunological findings

Abstract: Summary Three cases are described showing a seasonal exacerbation of their nephrotic syndrome in association with an atopic trait and grass pollen allergy. The first patient has a history of four consecutive seasonal relapses each requiring steroid therapy. Following a course of desensitization injections he has now been free of relapse for 3 consecutive years. The second patient has also had a recurrent steroid‐sensitive nephrotic syndrome often associated with the pollen season and allergic rhinitis. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…The role of hypersensitivity to environmental antigens in idiopathic nephrotic syndrome (INS) remains con troversial [1], Since 1957, there have been several isolated reports of relapses of INS following contact with respira tory antigens; because of the seasonal onset of these exacerbations, the first of these reported cases were asso ciated with pollens [2][3][4], Later, other respiratory anti gens such as mould [5], house dust [6] and wheat flour antigens [7] were incriminated. Although the number of such reported cases is small, Fontana et al [8] have documented a high incidence of atopy in INS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The role of hypersensitivity to environmental antigens in idiopathic nephrotic syndrome (INS) remains con troversial [1], Since 1957, there have been several isolated reports of relapses of INS following contact with respira tory antigens; because of the seasonal onset of these exacerbations, the first of these reported cases were asso ciated with pollens [2][3][4], Later, other respiratory anti gens such as mould [5], house dust [6] and wheat flour antigens [7] were incriminated. Although the number of such reported cases is small, Fontana et al [8] have documented a high incidence of atopy in INS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies pointed out the ST2 protein as a selective marker of Th2 cells [10][11][20][21] , which correlates with the atypical Th2 polarization described in INS [22][23][24] . Finally, sST2 seems to be tightly associated with allergic airways inflammation [12][13][14] , which have also been associated with some cases of nephrotic syndrome [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have associated INS with allergy risk of clinical and immunological features (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the 1950s through the 1970s, few anecdotal reports described patients who developed INS after allergic reactions to inhaled allergens, vaccinations, food, or insect stings (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Numerous studies have associated INS with allergy risk of clinical and immunological features (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the 1950s through the 1970s, few anecdotal reports described patients who developed INS after allergic reactions to inhaled allergens, vaccinations, food, or insect stings (2)(3)(4)(5). Since 1970, several case-control studies revealed that elevated serum IgE and atopic diathesis were more common in children with INS than non-INS controls (9,(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation